PENGGUNAAN PSIKOTERAPI SUFISTIK PADA REMAJA YANG MENGALAMI KECANDUAN GAME ONLINE DI KELURAHAN PASIR KIDUL [USING SUFISTIC PSYCHOTHERAPY FOR ADOLESCENTS WITH ONLINE GAME ADDICTION IN PASIR KIDUL SUB-DISTRICT] - Prasetyo Nugroho, Adhitya Ridwan Budhi; Khotimah, Khusnul (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2022)
In this modern era, human life is full of demands that create pressure, coupled with the erosion of the spiritual dimension and God’s vision within him, one of which is through online games. For this reason, it is necessary to treat emotional problems through Sufistic psychotherapy as a coaching effort to reduce mental stress. The purpose of this research is to describe the use of Sufistic psychotherapy in treating adolescents who are addicted to online games. The method used in this study is a qualitative method with a descriptive approach. The data collection techniques in this study are through interviews, observation and documentation. The findings of this study are the use of Sufistic psychotherapy in dealing with adolescents who are addicted to online games bringing about a change in adolescents in the Pasir Kidul Sub-District and in the process going through several stages of Sufistic psychotherapy such as pre-contemplation, contemplation, preparation, maintenance, and termination.